Advances in antiobesity mechanisms of capsaicin. (December 2021) - Wang, Yuanwei; Zhou, Yahan; Fu, Jia
Abstract: Obesity is a global epidemic that affects the lives and health of millions of people. The prevention and treatment of obesity have become a significant public health challenge worldwide. Numerous studies showed that the gut microbiota is associated with the development of obesity, and the regulatory mechanisms mediating the relationship between gut microbiota and obesity have become an intense research area. Capsaicin is a vanilla amide alkaloid that is an active ingredient in pepper. Much research demonstrated the antiobesity activity of capsaicin. This article reviews recent research on the antiobesity mechanisms of capsaicin involving alterations of the gut microbial composition, reduction of intestinal permeability, and regulation of the microbiome-gut-brain axis. This summary will establish a basis for further developing capsaicin as an ingredient in medications and health products.